Presentation for The Political Economy of Food System Transformation: Pathways to Progress in a Polarized World - Resnick, Danielle; Gómez, Eduardo; Barrett, Christopher B.; Swinnen, Johan (2023)
Amid rising geopolitical conflict, populism and nationalism, and clashes between empirical evidence and disinformation campaigns, many countries are trying to transform their food systems to achieve healthier, more sustainable outcomes. To accomplish this challenging goal, pathways to transform food systems must be grounded in a sound understanding of interest group dynamics, incentive systems, the role of ideology and coalitions, and accountability structures.